(untitled) (Journal of Current and Advance Medical Research, 2020)
Background: The diagnosis of chikungunya is confusing due to similar clinical presentations of different viral illnesses. Objective: The purpose of the present study was to evaluate the accuracy of an antibody-based test for the diagnosis of chikungunya infection Methodology: This cross-sectional study was conducted at the Department of Internal Medicine, Bangabandhu Sheikh Mujib Medical University, Dhaka, from July to September 2017 when an outbreak of chikungunya occurred in Bangladesh. Chikungunya patients were evaluated by the IgM antibody test by immunochromatographic method (ICT) during both the early phase and the convalescent-phase. The sensitivity and specificity of the IgM antibody test were estimated considering the polymerase chain reaction (PCR) method as the gold standard. Result: The sensitivity and specificity of the IgM antibody test in the acute phase were 2.7 percent and 79.5 percent, respectively. In contrast, in the convalescence phase, sensitivity and specificity were 86.5 percent and 33.3 percent. Conclusion: Antibody-based testing was found not suitable for detecting chikungunya infection during the acute phase of the illness. Journal of Current and Advance Medical Research 2020;7(2): 68-72